Estimating propulsive forces in front crawl swimming - Satkunskiene, D.; Lagunaviciene, N. (Education. Physical training. Sport, 2000)
The paper aims are to analyse the biomechanical estimating methods of propulsive forces in front crawl swimming, to evaluate their qualities and durations, to summarize the propulsive forces measuring data published in the last twenty years. The analysis shows that there are direct and indirect methods of estimating propulsive forces during free swimming. Direct methods have included force or pressure transducers on the hand, tethered and semi-tethered swimming and underwater force push-off pads. Such studies give no insight into the body segment rotations (joint actions) responsible for creating these propulsive forces. The indirect method of estimating propulsive forces from three-dimensional kinematic data developed by Schleihauf has been used extensively by researchers over the last twenty years. An important factor, affecting the validity of propulsive forces used the Schleihauf method, is the reliability of the kinematics from which the forces are computed. During the front crawl pull, the hand and forearm provide propulsion for the swimmer. Theoretical model of hand propulsion is used to analyse how the propulsive force depends on the speed, direction (path) and plan area of the hand and how movements of the head, trunk and upper extremity influence the hand paths and hand speeds. The analysis of literature revealed that two-dimensional analysis techniques are unable to describe fully and accurately the spatial movement patterns used by the swimmers.